Plunger surface multi-gradient diamond-like carbon film and preparation method thereof
By depositing a multi-gradient diamond carbon film on the surface of the plunger, the problem of wear of the plunger in harsh environments is solved, and the wear resistance and binding force are significantly improved, and the overall performance of the plunger is improved.
Patent Information
- Application Number
- CN202411600755.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-28
AI Technical Summary
The plunger is prone to wear in a harsh service environment, resulting in reduced fuel supply and insufficient engine power, affecting the service life and flight safety of the aircraft.
Multi-gradient diamond carbon films are deposited on the surface of the plunger, including Cr base layer, Cr+TiC or WC or TiCN transition layer, DLC layer doped with TiC or WC or TiCN, and DLC layer, and the unequilibrium dynamic closed electromagnetic field enhanced magnetron sputtering and electromagnetic enhanced PECVD deposition process.
It improves the wear resistance of the plunger surface, enhances the bonding force between the film and the plunger, ensures that the film does not fall off under high speed and high load conditions, and improves the hardness, low friction coefficient and wear resistance of the plunger.
Smart Images

Figure CN119710690A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of diamond-like carbon film preparation, and in particular relates to a multi-gradient diamond-like carbon film on a plunger surface and a preparation method thereof. Background Art
[0002] The plunger fuel pump in the aircraft engine is very important for the normal operation of the aircraft. It relies on the reciprocating motion of the plunger in its cylinder to achieve oil suction and discharge according to the change of the volume of the sealed working chamber. The plunger fuel pump is an important component of the aircraft engine fuel control system, and the performance of the plunger parts directly affects the performance and life of the aircraft engine control system. The plunger is a key component of the fuel pump. The service environment is harsh, which leads to wear on the plunger surface, reduced fuel supply, insufficient engine power, and ultimately affects the service life and flight safety of the aircraft. This requires the plunger to have excellent friction and wear properties. However, the currently commonly used alloy plungers themselves are difficult to meet such high performance requirements. Therefore, in order to improve the wear resistance of the plunger surface, it is urgent to modify the plunger surface to improve performance. Summary of the invention
[0003] Purpose of the Invention
[0004] In order to improve the wear resistance of the plunger surface, the present invention provides a method for preparing a multi-gradient diamond-like carbon film on the plunger surface.
[0005] Inventing technical solutions
[0006] A multi-gradient diamond-like carbon film on the plunger surface comprises, from the plunger surface outward, a Cr base layer, a Cr+TiC or WC or TiCN transition layer, a DLC doped with TiC or WC or TiCN, a DLC layer, and a DLC layer doped with TiC or WC or TiCN.
[0007] Preferably, the Cr base layer is prepared by unbalanced dynamic closed electromagnetic field enhanced magnetron sputtering.
[0008] Preferably, the Cr+TiC or WC or TiCN transition layer is deposited by enhanced magnetron sputtering.
[0009] Preferably, C2H2 is introduced when preparing a DLC layer doped with TiC or WC; and C2H2 and N2 are introduced when preparing a DLC layer doped with TiCN.
[0010] Preferably, the DLC layer is deposited by electromagnetically enhanced PECVD.
[0011] A method for preparing a multi-gradient diamond-like carbon film on a plunger surface comprises the following steps:
[0012] (1) Plasma activation cleaning of the plunger;
[0013] (2) Sputtering and depositing a Cr base layer, adjusting the Cr target current to 8 A, the argon gas flow rate to 100-300 sccm, the bias voltage to 30-100 V, and the deposition time to 15-40 min;
[0014] (3) Sputtering and depositing a Cr+TiC or WC or TiCN transition layer, adjusting the dynamic non-equilibrium magnetic field strength to 50 Gs, opening the target required for depositing the transition layer, and gradually reducing the Cr target current from 8 A to 1 A, and gradually increasing the target current required for depositing the transition layer from 1 A to 8 A, the bias voltage and argon gas flow rate are the same as in step (2), and the deposition time is 20-50 min; when sputtering and depositing the Cr+TiC or WC transition layer, 100-300 sccm C2H2 gas is filled, and when sputtering and depositing the TiCN transition layer, 100-300 sccm C2H2 and N2 gases are filled;
[0015] (4) Sputtering and depositing a DLC transition layer doped with TiC, TiCN or WC, turning off the Cr target, adjusting the argon gas flow rate to 150 sccm, keeping the bias voltage constant, and depositing for 30-60 min; when sputtering and depositing a DLC transition layer doped with TiC or WC, 100-300 sccm C2H2 gas is filled, and when sputtering and depositing a DLC transition layer doped with TiCN, C2H2 and N2 gases are filled;
[0016] (5) Deposit the DLC layer, turn off all targets, turn off the argon gas, adjust the C2H2 gas to 400-700 sccm, adjust the dynamic non-equilibrium magnetic field strength to 100 Gs, apply a negative bias of 500-800 V to the plunger sample, and deposit for 40-80 min;
[0017] (6) Depositing a DLC layer doped with TiC, TiCN or WC, turning on the required target, the target current is 1-3A, applying a negative bias of 30-100V to the plunger sample, depositing a DLC surface layer doped with TiC, TiCN or WC, the deposition time is 100-150min, cooling naturally, and finally obtaining a multi-gradient diamond-like carbon film on the plunger surface. When preparing the DLC layer doped with TiC or WC, a mixed atmosphere of 150sccm argon and 100-300sccm C2H2 is introduced. When preparing the DLC layer doped with TiCN, a mixed atmosphere of 150sccm argon, 100-300sccm C2H2 and N2 is introduced.
[0018] Preferably, the method uses an unbalanced dynamic closed electromagnetic field enhanced magnetron sputtering and an electromagnetic enhanced PECVD deposition vacuum system.
[0019] Preferably, during the plasma activation cleaning in step (1), the argon gas flow rate is 200-500 sccm, the acetylene gas flow rate is 100-600 sccm, the bias voltage is 500-800 V, and the processing time is 20-60 min.
[0020] Preferably, after plasma activation cleaning, the vacuum chamber is evacuated to reduce the background vacuum in the vacuum chamber to below 3×10-5Pa, argon gas is introduced, the gas pressure is adjusted to 0.3-1.5Pa, and then step (2) is performed.
[0021] Preferably, each target process parameter can be controlled independently.
[0022] Advantages of the present invention:
[0023] (1) The invention deposits a multi-gradient transition layer and a functional layer by a composite electromagnetic field enhanced magnetron sputtering process or a filtered cathode vacuum arc deposition process, and the prepared multi-gradient diamond-like film is firmly bonded to the surface of the plunger. Through a nano scratch test, it is measured that the maximum bonding force between the film and the plunger is about 60N, ensuring that the film does not fall off under high speed and high load conditions.
[0024] (2) The multi-layer gradient diamond-like film of the present invention is evenly distributed on the surface of the plunger and has relatively high hardness, low friction coefficient and excellent wear resistance. Under the premise of ensuring the hardness of the diamond-like film, the wear resistance of the plunger is improved by 1-3 times. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the structure of the multilayer gradient diamond-like film in Example 1.
[0026] Figure 2 This is a schematic diagram of the non-equilibrium dynamic closed electromagnetic field enhanced magnetron sputtering and electromagnetic enhanced PECVD deposition vacuum system used in Example 1.
[0027] Figure 3 This is a scanning electron microscope image of the multi-gradient diamond-like carbon film in Example 1.
[0028] Figure 4 This is the three-dimensional ultra-depth-of-field diamond carbon film surface morphology of Example 1.
[0029] Figure 5 This is the scratch image of the diamond carbon film of Example 1.
[0030] Figure 6 This is a graph of the friction coefficient of the diamond carbon film of Example 1.
[0031] In the figure, 1-Cr layer, 2-Cr+WC mixed layer, 3-WC-DLC layer, 4-DLC layer, 5-WC-DLC layer, 10-plunger, 11-magnetron cathode target 1, 12-magnetron cathode target 2, 13-magnetron cathode target 3, 14-magnetron cathode target 4, 15-filament 1, 16-filament 2, 17-central anode. DETAILED DESCRIPTION
[0032] The present invention is achieved through the following technical solutions.
[0033] A multi-gradient diamond-like carbon film on the plunger surface comprises, from the plunger surface outward, a Cr base layer, a Cr+TiC or WC or TiCN transition layer, a DLC doped with TiC or TiCN or WC, a DLC layer, and a DLC layer doped with TiC or TiCN or WC.
[0034] The preparation method of the diamond-like carbon film is to place the plunger after ultrasonic cleaning and plasma activation cleaning in a vacuum system of an unbalanced dynamic closed electromagnetic field enhanced magnetron sputtering and electromagnetic enhanced PECVD deposition system, and sequentially deposit multiple gradient transition layers, specifically:
[0035] A vacuum deposition system of non-equilibrium dynamic closed electromagnetic field enhanced magnetron sputtering and electromagnetic enhanced PECVD deposition is used, and a vacuum deposition device is formed by evenly distributing four pairs of targets, wherein the positions of magnetron cathode target 1 and magnetron cathode target 3 are Cr targets, and the positions of magnetron cathode target 2 and magnetron cathode target 4 are Ti or WC targets. The center of the deposition device is a central anode, and the hot filament plasma source system is located between the magnetron cathode target 1, magnetron cathode target 2 and the magnetron cathode target 3 and magnetron cathode target 4. The plunger is placed in the vacuum deposition system of non-equilibrium dynamic closed electromagnetic field enhanced magnetron sputtering and electromagnetic enhanced PECVD vapor deposition, and the dynamic closed magnetic field is adjusted to open the hot filament plasma source system to form a dense gas plasma between the hot filament plasma source system and the central anode, and plasma activation cleaning is performed, the argon gas flow rate is 200-500sccm, the acetylene gas flow rate is 100-600sccm, the bias voltage is 500-800V, and the processing time is 20-60min; the vacuum chamber is evacuated to reduce the background vacuum in the vacuum chamber to 3×10 -5 Pa, introduce argon gas and adjust the gas pressure to 0.3-1.5Pa.
[0036] (1) Depositing the Cr base layer by high-power unbalanced dynamic closed electromagnetic field enhanced magnetron sputtering, turning on targets 1 and 3, adjusting the target current to 8 A, the argon gas flow rate to 100-300 sccm, the bias voltage to 30-100 V, and depositing for 15-40 min;
[0037] (2) Deposition of Cr+TiC / or WC or TiCN transition layer by high-power unbalanced dynamic closed electromagnetic field enhanced magnetron sputtering. The dynamic unbalanced magnetic field strength was adjusted to 50 Gs. Targets 2 and 4 were turned on. The current of targets 1 and 3 was gradually reduced from 8 A to 1 A. The current of targets 2 and 4 was gradually increased from 1 A to 8 A. 100-300 sccm C was charged. 2 H 2 or N 2 The gas, bias voltage and argon flow rate remain unchanged and the deposition is carried out for 20-50 minutes;
[0038] (3) Sputtering and depositing a DLC transition layer doped with TiC, TiCN or WC, turning off targets 1 and 3, keeping the current and bias voltage of targets 2 and 4 unchanged, adjusting the argon gas flow rate to 150 sccm, and filling with 100-300 sccm C 2 H 2 or N 2 Gas, deposition 30-60min;
[0039] (4) Deposit the DLC layer by electromagnetically enhanced PECVD, turn off targets 2 and 4, and adjust C 2 H 2 The gas is 400-700sccm, the dynamic non-equilibrium magnetic field strength is adjusted to 100Gs, the negative bias voltage on the plunger sample is 500-800V, and the deposition is 40-80min;
[0040] (5) Deposition of DLC functional layer doped with TiC, TiCN or WC: Open targets 2 and 4, set the target current to 1-3A, and introduce 150sccm argon and 100-300sccm C 2 H 2 or N 2 Mixed atmosphere, a negative bias of 30-100V is applied to the plunger sample, a DLC surface layer doped with TiC or TiCN or WC is deposited, the deposition time is 100-150min, and the sample is cooled naturally, and finally a multi-gradient diamond-like carbon film is obtained on the plunger surface.
[0041] Example 1
[0042] The Cr12MoV plunger was ultrasonically cleaned in acetone and ethanol in sequence;
[0043] The plunger was placed in a composite electromagnetic field magnetron sputtering vapor deposition vacuum system for argon ion sputtering cleaning, with an argon gas flow rate of 220 sccm, a bias voltage of 600 V, and a processing time of 20 min;
[0044] The vacuum chamber was evacuated to reduce the background vacuum in the vacuum chamber to 3×10 -5 Below Pa;
[0045] Sputtering deposition of Cr base layer, open targets 1 and 3, adjust the target current to 3A, argon gas flow rate to 200sccm, bias voltage to 40V, deposition for 20min, the film thickness is about 147.8nm;
[0046] Sputtering deposition of Cr+WC transition layer, turn off target 3, turn on target 2, keep target current, bias voltage and argon gas flow unchanged, the film thickness is about 246.6nm after 30min deposition;
[0047] Sputtering deposition of WC-DLC transition layer, turn off target 1, turn on target 4, keep the current and bias voltage of targets 2 and 4 unchanged, adjust the argon gas flow rate to 150sccm, and fill with 100sccm C 2 H 2 Gas, deposition time 42 min, film thickness about 310.2 nm;
[0048] Deposit the DLC layer, turn off targets 2 and 4, and adjust C 2 H 2 The gas flow rate was 500 sccm, a negative bias of 600 V was applied to the plunger sample, and the deposition time was 60 min. The film thickness was about 493.2 nm.
[0049] Deposition of WC-doped DLC functional layer, open targets 2 and 4, argon and C 2 H 2 Mixed atmosphere, a negative bias of 40V is applied to the plunger sample, and the C 2 H 2 The WC-doped DLC surface layer was obtained by flow rate, the deposition time was 120 min, the film thickness was about 1043 nm, and it was cooled naturally. Finally, a multilayer gradient diamond-like carbon film was obtained on the surface of the plunger.
[0050] The nanoindentation test showed that the film had high hardness and elastic recovery. The friction test showed that the film had excellent friction performance, and its friction coefficient was 0.051 in the atmospheric environment.
[0051] Example 2
[0052] The Cr12MoV steel plunger was ultrasonically cleaned in acetone and ethanol in sequence;
[0053] The plunger was placed in a composite electromagnetic field magnetron sputtering vapor deposition vacuum system and cleaned by argon ion sputtering, with an argon gas flow rate of 230 sccm, a bias voltage of 600 V, and a processing time of 20 min;
[0054] The vacuum chamber was evacuated to reduce the background vacuum in the vacuum chamber to 3×10 -5 Below Pa;
[0055] Sputtering deposition of Cr base layer, open targets 1 and 3, adjust the target current to 3A, argon gas flow rate to 200sccm, bias voltage to 40V, deposition time to 22min, film thickness to about 151.4nm;
[0056] Sputtering deposition of Cr+TiCN transition layer, turn off target 3, turn on target 2, keep target current, bias voltage and argon flow unchanged, fill with 100 sccm C 2 H 2 and N 2Gas, deposition time 22min, film thickness is about 252.7nm;
[0057] The TiCN-doped DLC transition layer was sputtered and deposited. Target No. 1 was turned off and target No. 4 was turned on. The current and bias voltage of targets No. 2 and 4 remained unchanged. The argon gas flow rate was adjusted to 150 sccm. 2 H 2 and N 2 The flow rate remains unchanged, the deposition time is 45 minutes, and the film thickness is about 318.3 nm;
[0058] Deposit the DLC layer, turn off targets 2 and 4, and adjust C 2 H 2 The gas flow rate was 500 sccm, a negative bias of 700 V was applied to the plunger sample, and the deposition time was 62 min. The film thickness was about 506.1 nm.
[0059] Deposition of TiCN-doped DLC functional layer, open targets 2 and 4, argon, C 2 H 2 Mixed 2 Mixed atmosphere, a negative bias of 40V is applied to the plunger sample, and the C 2 H 2 and N 2 The flow rate was set to obtain a TiCN-doped DLC surface layer, the deposition time was 125 min, the film thickness was about 1076 nm, and it was cooled naturally. Finally, a multilayer gradient diamond-like carbon film was obtained on the plunger surface.
[0060] The nanoindentation test results show that the film has high hardness and elastic recovery. The friction test results show that the film has excellent friction performance. In the atmospheric environment, its steady-state friction coefficient is about 0.072.
[0061] The protection scope of the present invention is not limited to the above-mentioned embodiments. Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the scope of the present invention. If these changes and modifications fall within the scope of the claims of the present invention and their equivalents, the present invention is intended to include these changes and modifications.
Claims
1. A multi-gradient diamond-like carbon film on a plunger surface, characterized in that: From the surface of the plunger outward, there are Cr basic layer, Cr+TiC or WC or TiCN transition layer, DLC doped with TiC or WC or TiCN, DLC layer, and DLC layer doped with TiC or WC or TiCN.
2. A multi-gradient diamond-like carbon film on the plunger surface as claimed in claim 1, characterized in that: The Cr base layer was prepared by non-equilibrium dynamic closed electromagnetic field enhanced magnetron sputtering.
3. The multi-gradient diamond-like carbon film on the plunger surface as claimed in claim 1, characterized in that: The Cr+TiC or WC or TiCN transition layer is deposited by enhanced magnetron sputtering.
4. The multi-gradient diamond-like carbon film on the plunger surface as claimed in claim 1, characterized in that: When preparing a DLC layer doped with TiC or WC, C2H2 is introduced; when preparing a DLC layer doped with TiCN, C2H2 and N2 are introduced.
5. The multi-gradient diamond-like carbon film on the plunger surface as claimed in claim 1, characterized in that: The DLC layer was deposited by electromagnetically enhanced PECVD.
6. A method for preparing a multi-gradient diamond-like carbon film on a plunger surface as claimed in any one of claims 1 to 5, characterized in that: The steps include: (1) Plasma activation cleaning of the plunger; (2) Sputtering and depositing a Cr base layer, adjusting the Cr target current to 8 A, the argon gas flow rate to 100-300 sccm, the bias voltage to 30-100 V, and the deposition time to 15-40 min; (3) Sputtering and depositing a Cr+TiC or WC or TiCN transition layer, adjusting the dynamic non-equilibrium magnetic field strength to 50 Gs, opening the target required for depositing the transition layer, and gradually reducing the Cr target current from 8 A to 1 A, and gradually increasing the target current required for depositing the transition layer from 1 A to 8 A, the bias voltage and argon gas flow rate are the same as in step (2), and the deposition time is 20-50 min; when sputtering and depositing the Cr+TiC or WC transition layer, 100-300 sccm C2H2 gas is filled, and when sputtering and depositing the TiCN transition layer, 100-300 sccm C2H2 and N2 mixed gas is filled; (4) Sputtering and depositing a DLC transition layer doped with TiC, TiCN or WC, turning off the Cr target, adjusting the argon gas flow rate to 150 sccm, keeping the bias voltage constant, and depositing for 30-60 min; when sputtering and depositing a DLC transition layer doped with TiC or WC, 100-300 sccm of C2H2 gas is filled, and when sputtering and depositing a DLC transition layer doped with TiCN, 100-300 sccm of C2H2 and N2 mixed gas is filled; (5) Deposit the DLC layer, turn off all targets, turn off the argon gas, adjust the C2H2 gas to 400-700 sccm, adjust the dynamic non-equilibrium magnetic field strength to 100 Gs, apply a negative bias of 500-800 V to the plunger sample, and deposit for 40-80 min; (6) Depositing a DLC layer doped with TiC, TiCN or WC, turning on the required target, the target current is 1-3A, applying a negative bias of 30-100V to the plunger sample, depositing a DLC surface layer doped with TiC, TiCN or WC, the deposition time is 100-150min, cooling naturally, and finally obtaining a multi-gradient diamond-like carbon film on the plunger surface. When preparing the DLC layer doped with TiC or WC, a mixed atmosphere of 150sccm argon and 100-300sccm C2H2 is introduced. When preparing the DLC layer doped with TiCN, a mixed atmosphere of 150sccm argon, 100-300sccm C2H2 and N2 is introduced.
7. The method for preparing a multi-gradient diamond-like carbon film on a plunger surface as claimed in claim 6, characterized in that: The method adopts a non-equilibrium dynamic closed electromagnetic field enhanced magnetron sputtering and an electromagnetic enhanced PECVD deposition vacuum system.
8. The method for preparing a multi-gradient diamond-like carbon film on a plunger surface as claimed in claim 6, characterized in that: During the plasma activation cleaning in step (1), the argon gas flow rate is 200-500 sccm, the acetylene gas flow rate is 100-600 sccm, the bias voltage is 500-800 V, and the processing time is 20-60 min.
9. The method for preparing a multi-gradient diamond-like carbon film on a plunger surface as claimed in claim 6, characterized in that: After plasma activation cleaning, the vacuum chamber is evacuated to reduce the background vacuum in the vacuum chamber to 3×10 -5 Pa, introduce argon gas to adjust the gas pressure to 0.3-1.5 Pa, and then proceed to step (2).
10. The method for preparing a multi-gradient diamond-like carbon film on a plunger surface as claimed in claim 6, characterized in that: Each target process parameter can be controlled independently.